2008
DOI: 10.1007/s10531-008-9466-5
|View full text |Cite
|
Sign up to set email alerts
|

Exotic plant invasion in the highly degraded upland landscape of Hong Kong, China

Abstract: Plant communities in the continental tropics have suVered less from exotic plant invasions than their oceanic island counterparts. Most studies have focused on nearpristine communities. By contrast, we examine the resistance of semi-natural continental plant communities in Hong Kong, which have been suVering from chronic and massive human impacts. We compiled a list of all naturalized non-native species recorded in Hong Kong and then sampled the plant communities for exotic species along roadsides, a stream th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…This elevation effect was mediated by greater human activity in the lower elevations. A case study in Hong Kong (Leung et al 2009) lends support for our association of human activity and exotic species diversity in these Pinatubo canyons. They found that after centuries of anthropogenic disturbances, a greater number of exotic plant species was directly related to corridors of greater human impact and less-traveled sites were still relatively free of alien invasions.…”
Section: Environmental Control Of Cover and Structuresupporting
confidence: 52%
“…This elevation effect was mediated by greater human activity in the lower elevations. A case study in Hong Kong (Leung et al 2009) lends support for our association of human activity and exotic species diversity in these Pinatubo canyons. They found that after centuries of anthropogenic disturbances, a greater number of exotic plant species was directly related to corridors of greater human impact and less-traveled sites were still relatively free of alien invasions.…”
Section: Environmental Control Of Cover and Structuresupporting
confidence: 52%
“…Some may enter from the surrounding non-forest-most often agricultural-matrix, but the resistance of continental forests to such invasions is well-documented (e.g., [17,18]) ( Table 1). This resistance is usually attributed largely to dense shade [19], but may also reflect the preemption of other resources by a hyperdiverse native flora.…”
Section: Invasions Into Production Forests In the Tropicsmentioning
confidence: 99%
“…Land preparation requires careful control, due to the potential influence on seed germination [90]. Clear cutting of mature plantations creates large gaps that favour invasion [18,77]. Moreover, plantations trees may also become invasive (Table 3).…”
Section: Which Silvicultural Practices Favor Invasion?mentioning
confidence: 99%
“…for Hong Kong-Corlett 1992b;Dudgeon and Corlett 2004;Leven and Corlett 2004;Chung and Corlett 2006;for Singapore-Corlett 1988, 1992aTan et al 2007). In contrast, only single alien plant species, Syzygium jambos in Hong Kong (Leung et al 2009) and Clidemia hirta in Singapore (Teo et al 2003), have signiWcantly invaded native, closed-canopy forests. Additional aliens are established in the margins of some forest areas and along forest paths on both islands.…”
Section: Continental Islandsmentioning
confidence: 99%